Effect of three different diets on the population density and growth rate of rotifer, Brachionus plicatilis - Nurul Nadiah Abu Hasan (Terengganu: Universiti Malaysia Terengganu, 2013)
Rotifer, Brachionus plicatilis has been long known that they act as live food to the fish larvae which lack of DHA, EPA, and AA. There are three species of microalgae species used which are Nannochloropsis, Isochrysis, and Pavlova, to increase the biochemical composition of the rotifer also affect their population density, growth rate, and body size of the rotifer.